Quantitative comparison on the similarities and differences of Mongolian medicines in the treatment of liver diseases between China and Mongolia based on data mining - Huang, Congying; Zhou, Baochang; Chen, Aruhan; La, Budanbaila; Ye, Yu; Liu, Yibo; Zhang, Xinyu; Sun, Yanhong; Bo, Agula; Li, Minhui (Science of traditional Chinese medicine (Print), 2023)
Abstract Objective The R language was used to quantitatively compare the medication patterns of Mongolian medicines used for the treatment of liver diseases between China and Mongolia, with a view to provide a reference for the research and clinical application of Mongolian medicines in the treatment of liver diseases. Methods The Mongolian medicinal prescriptions used for treating liver disease in Mongolia were collected from the Mongolian Pharmacy and Mongolian Treatment Guide for Common diseases in Mongolian Medicine, and those used in China were collected from the Inner Mongolia Standard for Mongolian Proprietary Medicine and Annotation of Mongolian Medicine Preparation Specifications. After the database was established, the frequency, properties, and tastes of the Mongolian medicines were analyzed, and R studio was used for the association rules analysis and cluster analysis. Results A total of 27 prescriptions used in Inner Mongolia, China, were collected involving 105 Mongolian medicines, with a total frequency of 284. Among them, there were 18 high-frequency medicines (frequency ≥5), which had a frequency of 147, accounting for 51.76% of the total frequency. The medicine with the highest frequency (14, 4.93%) was Carthamus tinctorius L.. The analysis of the medicine data in China revealed 15 association rules. A total of 21 prescriptions used in Mongolia were collected, involving 92 Mongolian medicines, with a total frequency of 254. Among them, there were 17 high-frequency (frequency ≥5) medicines, with a total frequency of 124 (48.82%). The medicine with the highest frequency (13, 5.12%) was Carthamus tinctorius L.. The analysis of the medicine data in Mongolia revealed 79 association rules. In both regions, the high-frequency medicines used for treating liver disease commonly had cool or warm property with bitter or sweet taste. Conclusions Carthamus tinctorius L., Terminalia chebula Retz., and other Mongolian medicines are commonly used to treat liver diseases in Inner Mongolia and Mongolia. The Mongolian medicines with cool or warm property and bitter, sweet, or astringent taste are commonly used to protect the liver.